2021
DOI: 10.11648/j.ajetm.20210602.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Joint Multiple Agricultural Technology Production of Beans on Household Nutrition Outcome in East Africa

Abstract: This study analyzes the impact of beans produced under joint multiple agricultural technologies (Improved beans variety, soil carbon management, integrated pest control, and use of compost manure) on nutrition outcome of stunting, underweight, and wasting in Kenya, Uganda, and Tanzania. Adoption of technologies in East Africa has been in isolation only focusing on single technologies. However, farmers typically adopt joint multiple agricultural technologies as complements or substitutes thus technologies to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In another study, Hörner and Wollni (2021) found that household income as well as food security increased with the adoption of integrated technology in Ethiopian highlands. Using multinomial ESR approach, Levy and Ngeno (2021) also observed that combining multiple agricultural technologies can improve nutritional outcomes in wasting, underweight and stunting. These nutritional outcomes are related to a person's intake of food energy and nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Hörner and Wollni (2021) found that household income as well as food security increased with the adoption of integrated technology in Ethiopian highlands. Using multinomial ESR approach, Levy and Ngeno (2021) also observed that combining multiple agricultural technologies can improve nutritional outcomes in wasting, underweight and stunting. These nutritional outcomes are related to a person's intake of food energy and nutrients.…”
Section: Resultsmentioning
confidence: 99%